Memotret Kajian Ekonomi Islam di PTAI - Asyari, Asyari (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Over the past few years the study of Islamic economics are commonly carried out in line with the growth of Islamic financial institution. This study has encouraged the growth of Islamic economics literature with a variety of themes. This paper aims to describe the portrait of Islamic economics study in the Islamic College (PTAI) from the standpoint of academic works produced by graduates. There were 194 abstracts at the State Islamic Institute (STAIN) Bukittinggi, precisely in the Department of Islamic Economics analyzed using content analysis. The result of this study showed that Islamic economics was studied with various themes. Islamic financial institutions and financial products with a murabaha contract was at the top rank as the research theme. The findings of those studies encourage and strengthen the previous research, in addition to contributing toward the literature improvement. This study did not mean to say that the study of Islamic economics, particularly Islamic banking from academic research point of view has been drained, but it is expected that in the future the Islamic economics studies are more likely to be observed with a new approach, so that islamic economic studies is much more attractive.